Preliminary observations on the nesting of Barnacle Geese in Spitsbergen - Dittami, John; Thomforde, Charles; Kennedy, Scott (Wildfowl, 1977)
The behaviour of a colony of Barnacle Geese Branta leucopsis in Svalbard was observed during the last 10 days of incubation. The interactions between neighbouring geese in the nesting area during our observations can be summarized as follows: 1. Males defended certain areas around their nests and defended areas were contiguous. 2. Neighbouring males rarely attacked or threatened each other. They even tolerated certain other males, grazing inside their defended areas. 3. Neighbouring females were not tolerated by males in their territories whereas sitting females were not attacked on their nests in the absence of their mates and showed little alarm when neighbouring males came near the nest. The females were away from the nest for 5% of the time, most often between 07.00 and 13.00 hours.